COLD STRESS-INDUCED REGULATION OF DIFFERENTIALLY EXPRESSED GENES IN BARLEY (HORDEUM VULGAREL.) LEAVES - Ki-Won Lee; Md. Atikur Rahman; Y. Song; H. C. Ji; Gi J. Choi; Ki-Yong Kim; Sang-Hoon Lee (Journal of Animal and Plant Sciences, 2019)
Cold stress adversely affects the growth and development of plant. To identify cold stress-induced genes in barley leaves an annealing control primer (ACP)-based approach was applied. In this study, we identified cold induced-14 genes which were differentially expressed genes (DEG) in barley leaves. Total ten genes were up-regulated such as alcohol dehydrogenase gene (Adh2), cryptochrome 2 (Cry2) gene, SnRK1-type protein kinase(SnRK1),CHS gene for chalcone synthase (CHS), glyceraldehyde-3-phosphate dehydrogenase mRNA (GAPDH), dehydrin 9 (dhn9) gene, LHC II type I protein(LHCII), 17 kDa class I small heat shock protein (HSP17), and myo-inositol 1-phosphate synthase mRNA (MIPS). Two genes, alpha-tubulin 4 (atub4), metallothioneine type2 (mt2b) were down-regulated. Interestingly, cold-regulated another two homologues LHC IItype I protein (LHC II), and clone cortma-ap3were newly induced under cold stress. The identified genes are mostly involved in several biological functions including plant growth, photosynthesis, glycolysis, abiotic stress tolerance, and stress homeostasis in plants. The identified candidate genes would be suitable target for molecular breeding toward enhanced cold stress tolerance in plants.
Keywords: Cold stress; differentially expressed genes; Barley; Annealing control primer; Gene Fishing